Evaluation of Sub-acute toxicity and safety profile of Charmagaz seed oil in rats. - Anum Adil; Saira Saeed Khan; Sadaf Naeem; Ali Alqahtani; Taha Alqahtani; Ali Asgher Shuja; Anosh Tahir (PLoS ONE)
Charmagaz seed oil (CSO), derived from Cucurbitaceae family, and is a traditional mix of four different seeds: pumpkin, cucumber, watermelon, and musk melon. Widely utilized in Asia, this blend is considered as a brain tonic and a nutritional powerhouse. Despite its significant ethno medicinal value, the potential toxicity and safety of this combination oil have not been scientifically documented. Therefore, the current study was conducted to assess the sub-acute toxicity of Charmagaz seed oil in rat model for the assessment of its safety profile. For acute oral toxicity CSO was given at doses of 50, 500, and 5000 mg/kg orally over 28 days in rats. No evidence of toxicity was observed in animals when acutely exposed to CSO, implying that the LD50 is higher than 5000 mg/kg body weight. Cell viability assay revealed that Charmagaz oil is relatively non-toxic, showing an inhibition rate below 50% following 24 and 48-hour exposures. In the Brine Shrimp bioassay, oil demonstrated no cytotoxic effects, unlike the standard cytotoxic drug Etoposide, which resulted in 70% mortality at a 7.5 μg/ml concentration. No treatment-related toxicity or death was seen in any of the animals receiving dosages of 500 and 5000 mg/kg during the course of the 28-day study period, according to sub-acute oral toxicity tests. Additionally, no significant alterations (p > 0.05) were detected in hematological or biochemical parameters across the dosed groups. The administration of Charmagaz seed oil led to a modest elevation in high-density lipoprotein cholesterol, likely due to its polyunsaturated fatty acids content. Since the liver is a major organ involved in lipid metabolism hence, histopathological analysis was conducted to determine the effects of Charmagaz oil on hepatic tissues. The analysis revealed a positive correlation with biochemical results from liver function enzyme tests. Thus, this study provides evidence suggesting the safety of Charmagaz oil consumption at doses up to 5000 mg/kg.